Implementasi Pembuatan Eco-Friendly Soap Kepada Generasi Z: Indonesia - Nisrina, Ulfah Laila; Ambarwati, Auliah; Rifani, Riza Amalia (Celebes Journal of Community Services, 2024)
This program aims to empower students, specifically Generation Z, to become pioneers in applying zero waste principles. Through the production of eco-friendly soap, participants not only contribute to waste reduction but also experience various other benefits. By reducing the use of harmful chemicals in soap and its packaging, students can protect and improve their health. Moreover, the program offers a more economical solution, enabling students to manage resources more wisely. In the long term, this initiative contributes to environmental sustainability, fostering collective awareness of the importance of preserving the earth for future generations. Thus, the students of SMA Negeri 4 Parepare are not merely participants but also warriors who inspire positive change within their community.